Cadmium in cacao from Latin America and the Caribbean: A review of research and potential mitigation solutions - Meter, A.; Atkinson, R.J.; Laliberte, B. (Bioversity International, 2019)
Cadmium is a heavy metal which accumulates in the body and affects our health. In order to control the amount we consume, the EU has set maximum permissible levels for different foods. A regulation specifying maximum levels of cadmium in cocoa and chocolate products came into force in January 2019 and similar regulations are being developed by other countries. In comparison to other cacao growing regions such as Africa and Asia-Pacific, some countries of Latin America and the Caribbean (LAC) are particularly impacted by worrying levels of cadmium in cacao beans that are a concern for the manufacturers of high-cacao content products. In this context, there is a pressing need to identify solutions that reduce cadmium levels in cacao beans and provide mitigation solutions at key processing stages in the value chain.